ATP1A1 Integrates AKT and ERK Signaling via Potential Interaction With Src to Promote Growth and Survival in Glioma Stem Cells - Yu, Yang; Chen, Chen; Huo, Gang; Deng, Jinmu; Zhao, Hongxin; Xu, Rui; Jiang, Li; Chen, Song; Wang, Shali (Frontiers in Oncology, 2019)
Abstract Glioma stem cells (GSCs) have been considered to be responsible for treatment failure due to their self-renewal and limitless proliferative property. Recently, the Na+/K+-ATPase a1 (ATP1A1) subunit was described as a novel therapeutic target for gliomas. Interestingly, our previous proteomics study revealed that ATP1A1 is remarkably overexpressed in GSCs. In the current study, we investigated the role of ATP1A1 in regulating growth, survival, and tumorigenicity of primary human GSCs and the underlying molecular mechanism. We tested RNA and protein expression of ATP1A1 in glioma tissues and GSCs. In addition, we knocked down ATP1A1 in GSCs and assessed the effects thereof on growth, survival, and apoptosis. The role of ATP1A1 in signaling pathways was investigated in vitro. We found that the ATP1A1 expression level was associated with the grade of glioma. Knockdown of ATP1A1 in GSCs in vitro inhibited cell proliferation and survival, increased apoptosis, and halted cell-cycle progression at the G1 phase. Cell proliferation and survival were resumed upon rescue of ATP1A1 expression in ATP1A1-knockdown GSCs. The ERK1/2 and AKT pathways were inhibited through suppression of Src phosphorylation by ATP1A1 knockdown. Collectively, our findings suggest that ATP1A1 overexpression promotes GSC growth and proliferation by affecting Src phosphorylation to activate the ERK1/2 and AKT signaling pathways.